Intelligent Application for Detection of Departure of Mooring Angle (IDDOMA) - Beserdin, Nur Amirah (IRC, 2019)
This project focuses on to design a generic captures, analyze and evaluate of failure departure of mooring lines angle by using image processing. The system that can analyze and detect whether there are obvious shift of mooring lines that effect the departure angle with 4 camera photographs from a different angle from the top of the ship which is, two at the front of the ship and the other two from the back. The camera will be set up at the highest location on the ship to capture the overall view of the mooring lines angle. The main challenges that PETRONAS is currently facing is inability to effectively identify the movement of the mooring departure angle which will usually change depending on the environmental factor such as wind, wave and heavy storm and it will affect the crude product unloading processes where this was raised as an area of improvement after the recent Pabuk Typhoon incident that happened in early January 2019. Mooring system refers to a permanent structure to which a marine vessel will be secured. Moorings system is widely used in offshore and oil and gas industry especially to offload hydrocarbon liquid cargo that is not feasible to be at normal port or harbor due to the huge size of tankers and vessels. Refer to reality modelling similar to those by Bentley System called Context Capture is envisioned to be used as a mooring line and departure angles shift monitoring system as simple as taking a normal photograph from a hand-held camera, smartphones, tablet and even drones. By having this reality modelling to survey and monitor mooring line departure angle it will enhance the monitoring activity by providing accurate shift or tension deviation at a faster rate and thus accelerate decision making especially during adverse weather compared to current method that is only through tension detection. This type of monitoring has not been widely used yet especially for offshore industry and it is a great technology enhancement opportunity for PETRONAS to venture in line with global change nowadays towards image processing.